2020
DOI: 10.1021/acs.est.0c05860
|View full text |Cite
|
Sign up to set email alerts
|

Computational Assessment of the Three-Dimensional Configuration of Dissolved Organic Matter Chromophores and Influence on Absorption Spectra

Abstract: The three-dimensional configuration of dissolved organic matter (DOM) is an important factor in determining the role of DOM in natural and engineered systems, yet there is still considerable uncertainty regarding the formation and potential stability of molecular aggregates within DOM. In this paper, we describe a computational assessment of the three-dimensional configuration of DOM. Specifically, we were interested in evaluating the hypothesis that DOM forms thermodynamically stable molecular aggregates that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…When NTO is added to a solution containing LHA Red , it would first oxidize hydroquinones having the lowest reduction potentials and move onto hydroquinones of increasing potentials (and decreasing rate constants) as the reaction proceeds, resulting in deviations from the first-order behavior. (2) Physically, humic acid is a structurally dynamic, three-dimensional entity that undergoes constant conformational changes, such as aggregation, dissociation, and folding–unfolding, processes that are influenced by solution conditions such as pH, temperature, and ionic strength. As a result, only a portion of the total electrons stored in LHA Red would be exposed and accessible to solutes, such as NTO, at any given time. Additional reactive sites (i.e., hydroquinones) would become accessible over time through structural rearrangements of LHA and/or diffusion of NTO into the LHA interior.…”
Section: Resultsmentioning
confidence: 99%
“…When NTO is added to a solution containing LHA Red , it would first oxidize hydroquinones having the lowest reduction potentials and move onto hydroquinones of increasing potentials (and decreasing rate constants) as the reaction proceeds, resulting in deviations from the first-order behavior. (2) Physically, humic acid is a structurally dynamic, three-dimensional entity that undergoes constant conformational changes, such as aggregation, dissociation, and folding–unfolding, processes that are influenced by solution conditions such as pH, temperature, and ionic strength. As a result, only a portion of the total electrons stored in LHA Red would be exposed and accessible to solutes, such as NTO, at any given time. Additional reactive sites (i.e., hydroquinones) would become accessible over time through structural rearrangements of LHA and/or diffusion of NTO into the LHA interior.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a recent study utilizing molecular dynamics simulations concluded that DOM chromophores, including π−π stacked charge-transfer complexes, are generally solvent-accessible (<10% solvent-inaccessible). 29 Additional support for this idea comes from the study of Ferreira et al, which examined line broadening of hydrophobic stearic acid labeled with a nitroxide free radical (5-SASL). 30 In pH 3 humic substance solution (3 g/L), the electron spin resonance line width of 5-SASL became broader over the course of days, indicating partitioning of this probe into a more viscous, hydrophobic environment.…”
Section: ■ Discussionmentioning
confidence: 99%
“…For example, a study by Tinnancher and Honeyman utilizing tritiated borohydride to label SRFA reported that tritium was evenly distributed throughout different size fractions of SRFA (as measured by SEC), suggesting that borohydride was able to access and react with all DOM size fractions equally. Furthermore, a recent study utilizing molecular dynamics simulations concluded that DOM chromophores, including π–π stacked charge-transfer complexes, are generally solvent-accessible (<10% solvent-inaccessible) . Additional support for this idea comes from the study of Ferreira et al , which examined line broadening of hydrophobic stearic acid labeled with a nitroxide free radical (5-SASL) .…”
Section: Discussionmentioning
confidence: 99%
“…A potentially promising avenue for future research may be to examine the coating of clay mineral nanoparticles by the more complex SOM proxies recently proposed by Devarajan et al (2020) or Escalona et al (2021). However, we note that for such complex organic mixtures, the short timescale of typical MD simulations may be insufficient to obtain well equilibrated organic coatings, in which case the use of enhanced sampling techniques, such as replica-exchange MD simulations (Atmani et al, 2020;Vialykh et al, 2020), may be required.…”
Section: Discussionmentioning
confidence: 99%
“…(2021). However, we note that for such complex organic mixtures, the short time‐scale of typical MD simulations may be insufficient to obtain well equilibrated organic coatings, in which case the use of enhanced sampling techniques, such as replica‐exchange MD simulations (Atmani et al., 2020; Vialykh et al., 2020), may be required.…”
Section: Discussionmentioning
confidence: 99%